To solve the given quadratic equation:
\[ 4(x^2 - 7) - 10 = -13 \]
Let's simplify and solve step by step.
- Distribute the 4 in the equation:
\[ 4x^2 - 28 - 10 = -13 \]
- Combine like terms:
\[ 4x^2 - 38 = -13 \]
- Add 38 to both sides to isolate the \(4x^2\):
\[ 4x^2 = -13 + 38 \]
\[ 4x^2 = 25 \]
- Divide both sides by 4:
\[ x^2 = \frac{25}{4} \]
- Take the square root of both sides:
\[ x = \pm \sqrt{\frac{25}{4}} \]
\[ x = \pm \frac{5}{2} \]
Thus, the solutions for \(x\) are:
\[ x = \frac{5}{2} \quad \text{and} \quad x = -\frac{5}{2} \]
In simplest form, the solutions are:
\[ x = \frac{5}{2}, , -\frac{5}{2} \]